Circulation of HRSV in Belgium: from multiple genotype circulation to prolonged circulation of predominant genotypes. - Lieselot Houspie (Public Library of Science (PLoS), 2013)
Molecular surveillance of HRSV in Belgium for 15 consecutive seasons (1996-2011) revealed a shift from a regular 3-yearly cyclic pattern, into a yearly alternating periodicity where HRSV-B is replaced by HRSV-A. Phylogenetic analysis for HRSV-A demonstrated the stable circulation of GA2 and GA5, with GA2 being dominant over GA5 during 5 consecutive seasons (2006-2011). We also identified 2 new genotype specific amino acid mutations of the GA2 genotype (A122 and Q156) and 7 new GA5 genotype specific amino acid mutations (F102, I108, T111, I125, D161, S191 and L217). Several amino acid positions, all located in the second hypervariable region of HRSV-A were found to be under positive selection. Phylogenetic analysis of HRSV-B showed the circulation of GB12 and GB13, where GB13 represented 100% of the isolated strains in 4 out of 5 consecutive seasons (2007-2011). Amino acids under positive selection were all located in the aminoterminal hypervariable region of HRSV-B, except one amino acid located in the conserved region. The genotype distribution within the HRSV-B subgroup has evolved from a co-circulation of multiple genotypes to the circulation of a single predominant genotype. The Belgian GB13 strains circulating since 2006, all clustered under the BAIV branch and contained several branch specific amino acid substitutions. The demographic history of genotypes GA2, GA5 and GB13 demonstrated a decrease in the total GA2 and GA5 population size, coinciding with the global expansion of the GB13 population. The emergence of the GB13 genotype resulted in a newly established balance between the predominant genotypes.